Maltosa Mempertahankan Viabilitas Spermatozoa Epididimis Kerbau Belang yang Disimpan dalam Bentuk Cair - -, Yulnawati; Maheshwari, Hera; Rizal, Muhammad; -, Herdis (Jurnal Veteriner; Vol 11 No 2 (2010))
A study to determine the effect of maltose supplement in andromed based semen extender on theviability of buffalo’s epididymal spermatozoa following 12 and 24 hour storage as liquid semen. Epididymalspermatozoa were collected by combined methods of slicing, flushing and tissue pressure. The spermatozoawas then diluted with three different extenders, i.e Andromed only (A) as control, Andromed + 0.2% w/vMaltose (M1) and Andromed + 0.4% w/v Maltose (M2) as treatments. The percentages of progressivelymotil spermatozoa in the liquid semen in the following treatment of A, M1 and M2 were 48.33%; 53.33%and 55% respectively (after 12h of storage), and 45%; 46.67% dan 45% respectively (after 24h of storage).Besides, the percentage of live spermatozoa in A, M1 and M2 after 12h of storage were 70.33%; 72 % and72.33 % and after 24h of storage were 66.33%; 70% and 70.67 %. In conclusion, the addition of 0.2% and0.4% w/v maltose into Andromed extender could maintain the life of the spotted buffalo epididymalspermatozoa after storage for 4°C up to 24 hours.
Keywords: maltose, viability, epididymal spermatozoa, spotted buffalo